(untitled) (Chattagram Maa-O-Shishu Hospital Medical College Journal, 2021)
Background : Multisystem Inflammatory Syndrome in Children (MIS-C) is a serious condition that appears to be linked to Coronavirus Disease 2019 (COVID-19). Most children who become infected with the COVID-19 virus have only a mild illness. Aim of this study to evaluate the children who go on to develop MIS-C, some organs and tissues-such as the heart, lungs, blood vessels, kidneys, digestive system, brain, joints, skin or eyes -become severely inflamed. Case Report : 11 years old girl admitted in Paediatric Ward of in Imperial Hospital Chattogram on 12 July 2020 with the complains of fever, loose motion, rash in hands, body and legs, swelling of the wrist and ankle joints which were associated with anorexia, nausea , vomiting and bodyache. For this reason the child was evaluated. Conclusion : Clinical features in children have varied but predominantly include cardiac dysfunction, abdominal pain, and elevated inflammatory markers, including C-Reactive Protein (CRP) Ferritin, D-dimer and Interleukin-6. MIS-C can lead to shock and multiple organ failure requiring intensive care. Chatt Maa Shi Hosp Med Coll J; Vol.20 (2); July 2021; Page 89-92